What is the relation between tax avoidance and the firm value? The evidence from China - Zhou, Yichen (2022)
What is the impact of the tax avoidance on firm value? This paper intends to examine how tax avoidance activities influence the firm value of the listed firms in China. The traditional theory believes that tax avoidance transfers the wealth from the government to the shareholders and facilitates generating more firm value. However, some empirical studies including Desai and Dharmapala (2009) pointed out that this is not always the fact. Alternatively, they found that mainly owing to the agency problem, tax avoidance is negatively associated with the firm value in several different settings mainly owing to the fact that the wealth gained is offset by the costs incurred by the managerial discretion of the self-interested managers in tax avoidance activities. This paper intends to select 1449 listed non-financial service firms in China from 2010 to 2020 as the sample to further explore the effect of tax avoidance on firm value in the setting of China after the year 2010 to compare the finding with the previous empirical evidence so as to supplement the literature of the correlation between tax avoidance and firm value. Based on the regression results, this paper found that tax avoidance is negatively associated with the firm value, which is consistent with most of the previous empirical evidence regarding this topic. In addition, this paper also tests the role of corporate governance and found that the corporate governance mechanism is not able to always mitigate this negative impact after the robustness tests with another model.